Association of C-reactive protein (CRP) gene allelic variants with serum CRP levels and hypertension in Turkish adults - Komurcu-Bayrak, E.; Erginel-Unaltuna, N.; Onat, A.; Ozsait, B.; Eklund, C.; Hurme, M.; Mononen, N.; Laaksonen, R.; Hergenc, G.; Lehtimaki, T. (ELSEVIER IRELAND LTD, 2009)
Objective: Serum C-reactive protein (CRP) is an independent risk factor for cardiovascular disease and metabolic syndrome (MetS). The aim of this study was to analyze the CRP gene allelic variations in the Turkish adult risk factor (TARF) study and relate them with serum CRP levels as well as MetS and its components. Methods: We analyzed CRP gene polymorphisms (-286C>T>A [rs3091244], + 1444C>T [rs1130864], + 1059G>C [rs1800947], and +1846G>A [rs1205]) as well as their haplotypes, in addition to measuring CRP levels (n = 1138) and collecting risk factor data from 1987 adults (mean age 54.3 +/- 11.9 years, 51.3% women) participating in the TARF Study. MetS was defined by using the criteria of the National Cholesterol Education Program modified for pre-diabetes and in men for abdominal obesity. Results: After adjustment for the major cardiovascular risk factors, four CRP SNPs (-286C>T>A, +1059G>C, +1444C>T, and +1846G>A) were significantly associated with serum CRP levels in women (p T>A and +1444C>T polymorphisms were associated with CRP levels in men (p < 0.05). The haplotype analyses revealed four common CRP haplotypes. The haplotype 1 (CGCA) in women and the haplotype 3 (TGTG) in men were associated with serum CRP levels and hypertension (p < 0.05). However, no haplotype association was observed for MetS or its components. Conclusion: CRP gene allelic variation is associated with serum CRP levels as well as hypertension in Turkish adults. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Hypertension; C-reactive protein; Polymorphism; Haplotype; Turkish population; CORONARY-HEART-DISEASE; 3RD NATIONAL-HEALTH; METABOLIC SYNDROME; RISK-FACTORS; POLYMORPHISMS; DETERMINANTS; INFLAMMATION; DEFINITION; LONGEVITY; MORTALITY; Cardiovascular System & Cardiology